Marburg virus disease: a brief updated overview - Elhamalawy, Ahmed; Elgonaid, Rahaf (International Journal of Research in Medical Sciences, 2023)
The Marburg virus disease made headlines when Tanzania declared an outbreak on the 23rd of March 2023. Five deaths and three further cases were identified at the time of the announcement. Symptoms of Marburg virus can include fever, headache, muscle aches, vomiting, diarrhoea, and bleeding from various parts of the body, hence the similarity to Ebola which also causes a haemorrhagic fever. There is no specific treatment for Marburg virus, but supportive care can help manage symptoms and improve outcomes. This article aims to update physicians working in primary care on the presentation of Marburg virus disease as well as the latest updates in guidelines implemented to help with its management and prevention.